2017
DOI: 10.3892/br.2017.898
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between polymorphisms in the 3′untranslated region of the cyclin dependent kinase 6 gene and the human papillomavirus infection, and risk of cervical precancerous lesions

Abstract: The human papillomavirus (HPV) infection is essential for the development of cervical cancer and its precursor lesions. However, only certain persistently infected individuals develop cervical cancer. Cyclin-dependent kinase 6 (CDK6) is a critical regulatory cancer-associated gene in the cell cycle and in tumorigenesis. Single nucleotide polymorphisms (SNPs) in microRNA sites in the 3′-untranslated region (UTR) of target genes may result in target gene expression level changes and susceptibility to diseases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…It had been shown that SLIT2 expression levels were negatively correlated with the incidence of cervical cancer in patients treated with postoperative chemotherapy (CT) or radiotherapy (RT), indicating that SLIT2 may be a potential predictive biomarker [14] . Cyclin-dependent kinase6 (CDK6) was a crucial regulatory cancer-related gene within the cell cycle and tumorigenesis, the changes in the level of CDK6 expression may impact on the progression of cervical precancerous lesions in the female [15] . HPV integration frequency increases with severity of cervical precancer, and viral integrations are present in the majority of cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that SLIT2 expression levels were negatively correlated with the incidence of cervical cancer in patients treated with postoperative chemotherapy (CT) or radiotherapy (RT), indicating that SLIT2 may be a potential predictive biomarker [14] . Cyclin-dependent kinase6 (CDK6) was a crucial regulatory cancer-related gene within the cell cycle and tumorigenesis, the changes in the level of CDK6 expression may impact on the progression of cervical precancerous lesions in the female [15] . HPV integration frequency increases with severity of cervical precancer, and viral integrations are present in the majority of cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that SLIT2 expression levels were negatively correlated with the incidence of cervical cancer in patients treated with postoperative chemotherapy (CT) or radiotherapy (RT), indicating that SLIT2 may be a potential predictive biomarker [ 42 ]. Cyclin-dependent kinase6 (CDK6) was a crucial regulatory cancer-related gene within the cell cycle and tumorigenesis, the changes in the level of CDK6 expression may impact on the progression of cervical precancerous lesions in the female [ 43 ]. HPV integration frequency increases with severity of cervical precancer, and viral integrations are present in the majority of cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This lower susceptibility to cervical lesions was also observed to rs8179 GA, compared to AA genotype and rs42033 AT, compared to AA genotype, after adjustments for HPV infection and others clinical and demographic characteristics. Strong linkage disequilibrium values were observed between rs8179, rs4272, rs42033 and rs42377 and the haplotype AGTA was significantly associated to a reduced risk to precancerous cervical lesions when compared to GAAG haplotype ( 150 ).…”
Section: Viral Infections and Polymorphic Variants That Affect Mirnasmentioning
confidence: 95%
“…Various miRNAs are reported to be involved in CDK6-mediated tumorigenesis, such as miR-145, miR-320, and miR-29. In a Chinese population, Ye et al ( 150 ) studied for the first time the effect of five genetic variations in the 3′UTR of CDK6 gene (rs8179 G/A, rs4272 A/G, rs42033 A/T, rs42035 T/C, and rs42377 G/A) on susceptibility to precancerous cervical lesions. The authors found that the rs8179 A and rs42033 T alleles were associated to a lower risk to develop precancerous cervical lesions and had an antagonistic interaction with the HPV infection.…”
Section: Viral Infections and Polymorphic Variants That Affect Mirnasmentioning
confidence: 99%